Synergism of crude extracts and essential oils from medicinal plants with antimicrobial drugs - Silva, Nathalia Cristina Cirone [UNESP]; Barbosa, Lidiane Nunes [UNESP]; Andrade, Bruna Fernanda Murbach Teles [UNESP]; Probst, Isabela da Silva [UNESP]; Doyama, Julio Toshio [UNESP]; Fernandes Junior, Ary [UNESP] (My University, 2013)
The emergence of resistant strains to conventional antimicrobial drugs has been constant as well as research aimed new alternatives of antibacterial agents. Therefore, considering that natural products have been an important potential source of new antimicrobial drugs, aim to verify the synergism by disk and time kill curve method between antimicrobials (extracts-Ext. and essential oils-EO) from four plant and eight antimicrobial drugs against Staphylococcus aureus and Escherichia coli strains from human specimens. The S. aures strains were highly susceptible with all plant antimicrobials (eg., 1.24 mg/ml with Vernonia polyanthes Ext. and 2.21 mg/ml with Eugenia uniflora EO for the Minimal Inhibitory Concentration-MIC). According disk method, the Bacharis dracunculifolia and V. polyanthes EO had synergism with all eight tested drugs while only Matricaria chamomilla Ext. showed synergism against S. aureus. The synergism was found with V. polyanthes and E. uniflora Ext. while M. chamomilla Ext. had antagonism against E. coli strains. By time kill curve, the bacterial growth inhibition was superior when drugs were tested alone and the synergism effect also was verified. The antagonism effect was detected only for E. coli strains and only with Ext. Results indicated the potential use of these products as coadjutants during treatment of infectious diseases.
Keywords: Antimicrobial activity; Essential oils; Methanolic extract; Medicinal plants; S. aureus; E. coli; P. Aeruginosa